Cochlear Pericytes Are Capable of Reversibly Decreasing Capillary Diameter In Vivo After Tumor Necrosis Factor Exposure. Issue 10 (December 2017) - Bertlich, Mattis; Ihler, Friedrich; Weiss, Bernhard G.; Freytag, Saskia; Strupp, Michael; Canis, Martin
Abstract : Objective: The aim of this work was to evaluate the effect of tumor necrosis factor (TNF) and its neutralization with etanercept on the capability of cochlear pericytes to alter capillary diameter in the stria vascularis. Methods: Twelve Dunkin–Hartley guinea pigs were randomly assigned to one of three groups. Each group was treated either with placebo and then placebo, TNF and then placebo, or TNF and then etanercept. Cochlear pericytes were visualized using diaminofluorescein-2-diacetate and intravasal blood flow by fluorescein-dextrane. Vessel diameter at sites of pericyte somas and downstream controls were quantified by specialized software. Values were obtained before treatment, after first treatment with tumor necrosis factor or placebo and after second treatment with etanercept or placebo. Results: Overall, 199 pericytes in 12 animals were visualized. After initial treatment with TNF, a significant decrease in vessel diameter at sites of pericyte somas (3.6 ±4.3%, n = 141) compared with placebo and downstream controls was observed. After initial treatment with TNF, the application of etanercept caused a significant increase (3.3 ±5.5%, n = 59) in vessel diameter at the sites of pericyte somata compared with placebo and downstream controls. Conclusion: We have been able to show that cochlear pericytes are capable of reducing capillary diameter after exposition to TNF. Moreover, the reduction in capillary diameter observed after the application of TNF is revertible after neutralization of tumor necrosis factor by the application of etanercept. It seems that contraction of cochlear pericytes contributes to the regulation of cochlear blood flow. Abstract : Supplemental Digital Content is available in the text